2005
DOI: 10.1016/j.immuni.2004.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Neutralizing Anti-HIV Antibody 4E10 Recognizes a Helical Conformation of a Highly Conserved Fusion-Associated Motif in gp41

Abstract: Broadly neutralizing monoclonal antibodies to HIV-1 are rare but invaluable for vaccine design. 4E10 is the broadest neutralizing antibody known and recognizes a contiguous and highly conserved epitope in the membrane-proximal region of gp41. The crystal structure of Fab 4E10 was determined at 2.2 A resolution in complex with a 13-residue peptide containing the gp41 core epitope (NWFDIT). The bound peptide adopts a helical conformation in which the key contact residues, TrpP672, PheP673, IleP675, and ThrP676, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
451
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 411 publications
(467 citation statements)
references
References 47 publications
15
451
1
Order By: Relevance
“…The extended helical structure of an MPER peptide, KWASLWNWFNITNWLWYIK in DPC micelles was also revealed by an NMR study offering a model of possible interaction of this region with the membrane [45]. More recently, a crystal structure of a 4E10 Fab in complex with a peptide bearing the sequence, WNWFDITNW revealed its major contact residue segment, WFDIT to be in a helical conformation [46]. A further study showed improved 4E10 binding affinity to a helix-stabilized peptide relative to the starting untethered peptide [47].…”
Section: Introductionmentioning
confidence: 93%
“…The extended helical structure of an MPER peptide, KWASLWNWFNITNWLWYIK in DPC micelles was also revealed by an NMR study offering a model of possible interaction of this region with the membrane [45]. More recently, a crystal structure of a 4E10 Fab in complex with a peptide bearing the sequence, WNWFDITNW revealed its major contact residue segment, WFDIT to be in a helical conformation [46]. A further study showed improved 4E10 binding affinity to a helix-stabilized peptide relative to the starting untethered peptide [47].…”
Section: Introductionmentioning
confidence: 93%
“…These core epitopes were determined by peptide mapping; however, alanine-scanning mutagenesis of the MPER in intact viruses established that only a few residues (D664/K665/W666, W672/F673/W680, and N671/ D674 HXB2 numbering throughout) are essential for 2F5, 4E10, and Z13e1 neutralization, respectively (7,9). Crystal structures of Fab 2F5, 4E10, and Z13e1 complexed with their respective epitope peptides subsequently confirmed that residues DKW, WFW, and ND are buried in the paratopes of these antibodies (10)(11)(12)(13)(14).…”
mentioning
confidence: 93%
“…We opted to first mutate residues at the apex of the CDRH3 because previously described crystal structures of Fab 4E10 complexed to an epitope peptide revealed that this region does not form part of the antigen binding site as is often the case for a CDRH3 (14,30). A similar study was not implemented for 2F5, because the case for 2F5-lipid interactions is less clear, its very occurrence a topic of current debate (21,27,31).…”
mentioning
confidence: 99%
“…Moreover, much of the antibody response may be to rearranged or dissociated forms of gp120 and gp41, on which the dominant epitopes may be either in hypervariable loops or in positions occluded on virion-borne envelope trimer. Rare, ''broadly neutralizing'' antibodies have been detected that recognize one of three relatively conserved regions on the envelope protein: the CD4-binding site (mAb b12) (2); carbohydrates on the outer gp120 surface (mAb 2G12) (3); and a segment of the gp41 ectodomain adjacent to the viral membrane (mAbs 2F5 and 4E10) (4,5), often called the ''membrane-proximal external region'' (MPER). We seek to understand the molecular mechanisms of neutralization by these and other antibodies.…”
mentioning
confidence: 99%